Do women entrepreneurs practice a different kind of entrepreneurship? - Theaker, Alison (Emerald Publishing Limited, 2024)
Whilst the number of women-owned enterprises has been increasing, they account for only 35% of business ownership in the UK. The term "woman entrepreneur" is suggested to be somewhat problematic, as it seems that women simply practise entrepreneurship, challenging the preconceptions people may have about businesses run by women. Do Women Entrepreneurs Practice a Different Kind of Entrepreneurship? identifies the entrepreneurship model of successful women entrepreneurs, and if they support or diverge from mainstream definitions. Alison Theaker examines female entrepreneurs' experiences to understand whether their entrepreneurship practices conform to existing models, and whether the concept of "success" has different meanings for such businesses than in mainstream entrepreneurial theory.
Includes index.
Keywords: Businesswomen.; Entrepreneurship.; Business & Economics, Women in Business.; Entrepreneurship, Start-ups.; Business and Management.; Gender studies: women and girls.; elektronické knihy; electronic books